Influence of crystallinity and surface area on the hydration kinetics of CA2 - Hüller, Florian; Ectors, Dominique; Neubauer, Jürgen; Götz-Neunhoeffer, Friedlinde (Cement and Concrete Research, 2016)
The hydration of CA (CaAlO) is usually a slow process. However, we found that CA is easily grindable and that the BET surface area and the amount of X-ray amorphous phase highly influence the hydration kinetics. Tempering of ground samples significantly decreased the BET surface area and the amount of X-ray amorphous phase. The hydration of tempered CA started later and proceeded much more slowly. A different degree of crystallinity of CA explains the wide range of different hydration kinetics and especially the occurrence of the often observed exothermic heat flow peak prior to the CA main reaction. By different grinding procedures and tempering we were able to prepare samples that were completely hydrated within 24 h and such samples which did not react within 24 h. Using heat flow calorimetry, in-situ XRD and in-situ H-TD-NMR we show that X-ray amorphous CA reacts prior to crystalline CA.
Keywords: Amorphous material (B); Calcium aluminate cement (D); Calorimetry (A); Hydration (A); X-ray diffraction (B)